2020
DOI: 10.1021/acsami.0c10784
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Antioxidation Capability of the Ni Catalyst by Carbon Shell Coating for Alkaline Hydrogen Oxidation Reaction

Abstract: Increasing the antioxidation capability of Ni for the hydrogen oxidation reaction (HOR) is considered important and challenging for alkaline polymer electrolyte fuel cells (APEFCs). Herein, we report a series of Ni-core carbon-shell (Ni@C) catalysts obtained by a vacuum pyrolysis method treated at different temperatures. According to the cyclic voltammetry tests and the HOR tests, Ni@C treated at 500 °C exhibits a much higher Ni core utilization and better catalytic activity toward HOR than the commonly used N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 38 publications
0
40
0
Order By: Relevance
“…Considering this aspect, Cherevko and co-workers investigated the chemical and electrochemical stability of representative Ni-based catalysts including monometallic Ni and bimetallic Ni 3 M (M = Co, Fe, Cu, Mo) nanoparticles in alkaline electrolytes by using in situ and ex situ techniques. [136] As shown in Figure 13a,b, different behaviors are observed on the catalysts. More specifically, Mo was dissolved from Ni 3 Mo/C in the potential window at 0-0.3 V RHE , while the Cu in Ni 3 Cu/C was stable below E = 0.4 V versus RHE, but underwent noticeable electrochemical transient dissolution above this potential.…”
Section: Improvement Of the Chemical Stability Of Hor Catalystsmentioning
confidence: 93%
See 2 more Smart Citations
“…Considering this aspect, Cherevko and co-workers investigated the chemical and electrochemical stability of representative Ni-based catalysts including monometallic Ni and bimetallic Ni 3 M (M = Co, Fe, Cu, Mo) nanoparticles in alkaline electrolytes by using in situ and ex situ techniques. [136] As shown in Figure 13a,b, different behaviors are observed on the catalysts. More specifically, Mo was dissolved from Ni 3 Mo/C in the potential window at 0-0.3 V RHE , while the Cu in Ni 3 Cu/C was stable below E = 0.4 V versus RHE, but underwent noticeable electrochemical transient dissolution above this potential.…”
Section: Improvement Of the Chemical Stability Of Hor Catalystsmentioning
confidence: 93%
“…Increasing the anti-oxidation capability of Ni for the hydrogen oxidation reaction (HOR) is also considered by Zhuang and co-workers. [136] They synthesized a series of Ni@C catalysts by vacuum pyrolysis at different temperatures. The HOR tests show the Ni@C catalyst obtained at 500 °C exhibits the highest Ni utilization and the best HOR catalytic performance.…”
Section: Electronic Structure Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 83 ] Therefore, a major task is to preserve the metallic Ni sites so as to achieving long‐term durability. Surface coating is a simple but effective method to mitigating the surface oxidation of Ni under alkaline HOR condition as the metallic Ni surface does not directly contact with the alkaline solution; [ 98 ] however, the HOR process is also inhibited. On the other hand, it was demonstrated that the inner metallic core can activate the outer graphene layers via electronic interaction, [ 99 ] and hence the electrocatalytic activity is preserved.…”
Section: Non‐pgm Electrocatalysts For the Alkaline Hormentioning
confidence: 99%
“…The h-BN shells help to maintain the active metallic Ni phase in both air and the electrolyte, and it also weakens the interactions of the O, H, and OH species with the Ni surface. Zhuang et al 118 synthesized the Ni@C catalysts by a vacuum pyrolysis method, and the antioxidation capability of Ni has been improved by the carbon shells. The graphitization degree of the carbon shells is the key factor affecting Ni utilization and its HOR activity.…”
Section: Nickel-based Catalystsmentioning
confidence: 99%